BUMDes Information System Mukti Bersama - M Zaenal Arifin; Agnes Novita (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
Village is the smallest form of government in the Republic of Indonesia, whose growth is very important in supporting the growth of the country evenly. Village-Owned Enterprises (BUMDes) play an important role in the development of a village and as a forum for encouraging community economic growth. Utilization of information technology is needed so that transaction recording is carried out quickly and produces accurate reports so that the management of BUMDes is better. This study uses a prototyping development method to help BUMDes Mukti Bersama management understand the system needed. The result of this study is a BUMDes information system that integrates data from three business units at BUMDes Mukti Bersama and is able to produce fast and accurate financial reports.